2017
DOI: 10.5505/iuyd.2017.91885
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting consumers' intention to purchase online

Abstract: The purpose of this study is to identify the effects of factors affecting consumers' intention to purchase from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…According to (Eyyup, at. Al, 2017) [32], Purchase Intention has a positive and significant influence on online Purchase Behavior. According to (Grecia at.…”
Section: Conceptual Framework and Research Hypothesismentioning
confidence: 99%
“…According to (Eyyup, at. Al, 2017) [32], Purchase Intention has a positive and significant influence on online Purchase Behavior. According to (Grecia at.…”
Section: Conceptual Framework and Research Hypothesismentioning
confidence: 99%
“…The Duplication of Purchase also suggests that any partition or groupings of e‐brands within a product category might come down to functional differences or dissimilarities of end‐users. Research that has examined online competition found that product variety (Chang, 2011; Sethi et al, 2018; Yaraş et al, 2017), price (Bucko et al, 2018; Usman & Kumar, 2020; Yaraş et al, 2017) and availability of a physical store (Yaraş et al, 2017) might impact the consumer intention to purchase online. In a similar vein, studies comparing buying behaviour for different online sub‐markets, such as private and public e‐banks, attributed any differences to user intentions and satisfaction (Agrawal et al, 2017; Hada, 2016; Raveendran, 2016).…”
Section: Background and Research Questionsmentioning
confidence: 99%
“…There have been studies on many factors affecting online shopping, but among them, research on consumers' online shopping intentions and online shopping behaviors/ attitudes is remarkable. Changes due to the quality of the platform/digital media/ web page/application where the online shopping is done, consumer personal and demographic characteristics, product/service quality and other external factors (Li and Zhang, 2002), perceived benefit, perceived risk, interest in e-commerce, evaluations on the offer (Teo, 2002), product and product diversity, financial risk, suitability, price awareness, and accessibility in the physical store (Yaraş et al, 2017) are the factors that affect online shopping. Alghaith et al (2010) argued that some online media tools could affect consumers' online shopping attitudes.…”
Section: Factors Of Affecting Online Purchasingmentioning
confidence: 99%